2013
DOI: 10.1111/1574-6968.12233
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding the commercial Chinese caterpillar fungus

Abstract: Chinese caterpillar fungus (Ophiocordyceps sinensis) has been widely used as tonic in Asian medicine. Considering its curative effect and high cost, various counterfeit versions of O. sinensis have been introduced and are commercially available. These counterfeits have morphological characteristics that are difficult to distinguish based on morphology alone, thereby causing confusion and threatening its safe use. In this study, internal transcribed spacer (ITS) sequences as a DNA barcode were analyzed and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…DNA barcoding has been widely used to identify herbs in recent years. Xiang et al ( 2013 ) accurately identified 131 Ophiocordyceps sinensis (Berk.) G. H. Sung samples, as well as 12 common counterfeits and its closely related species by using DNA barcoding.…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding has been widely used to identify herbs in recent years. Xiang et al ( 2013 ) accurately identified 131 Ophiocordyceps sinensis (Berk.) G. H. Sung samples, as well as 12 common counterfeits and its closely related species by using DNA barcoding.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Therefore, Bhutanese Cordyceps was further identified using DNA barcoding method, which has been widely applied for species identification of animals, plants and fungi1718. Indeed, the nuclear ribosomal internal transcribed spacer (ITS) region has been considered as a universal DNA barcode marker for fungi identification19.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was extracted from the resulting powders using a Tiangen Plant DNA Kit (Tiangen Biotech, China). The ITS regions were amplified using an LA Taq polymerase chain reaction (PCR) kit (Takara Biotech Inc.) with the universal primer pairs 5F (5′-GGAAGTAAAAGTCGTAACAAGG-3′)/4R (5′-TCCTCCGCTTATTGATATGC-3′; Li et al, 2013). The PCR mixture contained 0.1 μL of LA Taq (5 U μL −1 ), 2.5 μL of 10 × LA Taq PCR buffer II (Mg 2+ Plus), 1 μL of dNTP mixture (2.5 mM each), 0.6 μL of each primer (10 μM), and 1 μL (~120 ng) of genomic DNA in a total volume of 25 μL.…”
Section: Methodsmentioning
confidence: 99%